Evidence Synthesis and Knowledge Integration for Sustainable Peatland Management - Kate Flood; David Wilson; Florence Renou-Wilson (Land, 2025)
Peatland research has expanded rapidly in the last two decades encompassing a diverse, multi-disciplinary evidence base, as countries seek to manage this resource sustainably along with meeting climate and biodiversity targets. There is growing global interest in the role of peatlands in carbon and water cycles, leading to more interdisciplinary research that applies ecosystem services and other integrative frameworks to generate knowledge and provide guidance for action. These trends have been replicated in Ireland with increasing research in peatland science, applied work on these degraded ecosystems, and a growing interest from civil society, landowners, and communities in the stewardship of this resource. This paper presents evidence-based insights from over two decades of Irish peatland research, with practical lessons for peatland policy and management in other national contexts. Analyses of the evidence from the literature, specialist expertise, and stakeholder knowledge were carried out under ten themes: biodiversity, soil, climate change, water, archaeology and palaeoenvironment, technology and mapping, society and culture, management, growing media and policy and law. The research identified four foundational pillars (accountability, longevity, equity and holistic knowledge) as critical to achieving sustainable peatland management in Ireland, with broader application to other regions. Peatland restoration is widely recognised across research disciplines as a key tool to meet regulatory targets related to climate, biodiversity, and water quality, while also delivering societal benefits. The findings of this research provide accessible, reliable and up-to-date evidence for sustainable peatland management. This study addresses a critical global knowledge gap by developing a novel, interdisciplinary evidence synthesis framework—applied here to Ireland but replicable worldwide—that systematically integrates 20 years of multi-disciplinary peatland research, expert insights, and stakeholder perspectives across ten thematic pillars.